Digital technology and privacy attitudes in times of COVID-19: formal legality versus legal reality in Ireland - Suriyawongkul, Arthit (My University, 2022)
The adoption of digital technologies to counteract the spread of COVID-19 has resulted in a major exposure of our rights to privacy and data protection. An empirical study conducted in Ireland by the Science Foundation Ireland-funded project PRIVATT demonstrates that privacy attitudes have shifted, resulting in a greater willingness to share personal data in order to combat the pandemic, while, at the same time, upholding a persistent mistrust in the public and private institutions overseeing this global health crisis. This article interprets these findings from a socio-legal perspective, arguing that people tend to overlook the inalienable nature of the essence of their rights to privacy and data protection, the compression of which is not admissible under EU law. Moreover, the widespread mistrust of public and private actors evidences a divergence between the formal legality of the technological solutions adopted and the legal reality that brings about the Irish public’s perception of government measures as potentially infringing their fundamental rights. These considerations will prompt recommendations in pursuit of enhancing transparency, involvement in decision-making processes and data protection literacy amongst the population.
Keywords: digital technology; privacy and data protection; efficiency; essence of fundamental rights; formal legality; legal reality; transparency; fundamental rights literacy; COVID-19; Digital Engagement; Inclusive Society; CIVIL RIGHTS; COVID-19; DATA PROTECTION; EU General Data Protection Regulation; Freedom of expression and privacy rights; Health Records; ICT and Privacy; Ireland; PRIVACY; PUBLIC ATTITUDES; PUBLIC HEALTH; Privacy Law; SURVEILLANCE; data privacy; Attitudes; Health; Justice and safeguarding; Policy